PENGARUH ENTERPRISE RISK MANAGEMENT, KEBIJAKAN HUTANG DAN SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN : PENGARUH ENTERPRISE RISK MANAGEMENT, KEBIJAKAN HUTANG DAN SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Adeliani Mathildis Riberu; Virna Sulfitri (Jurnal Ekonomi Trisakti, 2023)
The purpose of this study is to provide empirical evidence regarding the effects of Debt Policy, Sustainability Report, and Enterprise Risk Management. This study's sample consists of companies listed on the IDX between 2017 and 2021 that fall into the manufacturing sector of the Consumer Goods Industry. This study used IBM SPSS version 23 and multiple linear regression analysis to collect data from 20 businesses for a total of 100 observations, which met the requirements for testing the hypothesis. The findings indicate that the sustainability report, enterprise risk management, and foreign ownership have a significant positive impact on firm value.